Pengembangan Chatbot untuk Layanan Konsultasi Hukum dengan OpenAI GPT-4 - Arif Pria Purnama; Mutaqin Akbar (Universitas PGRI Kanjuruhan Malang, 2026)
The development of information and communication technology has encouraged the use of artificial intelligence in various fields, including legal consultation services. In Indonesia, legal consultation services still face several challenges, such as a limited number of legal experts, relatively high consultation costs, and unequal access, making it difficult for the public to obtain basic legal understanding. This study aims to develop an intelligent chatbot for legal consultation services using the OpenAI GPT-4 Application Programming Interface (API). The research methodology includes problem scope determination, user needs analysis, legal data collection, data exploration and pre-processing using Natural Language Processing (NLP) techniques, GPT-4-based chatbot modeling, and system evaluation. The evaluation focuses on measuring the chatbot’s response time in delivering legal information to users. The results indicate that the chatbot developed using the OpenAI GPT-4 API is able to provide basic legal information quickly and interactively. However, human supervision is still required to ensure the accuracy and reliability of the legal information provided.